Kinerja Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Klungkung Dalam Pelaksanaan Program Begitu Lahir Anak Mendapatkan Akta Kelahiran (Bela Nanda) - Sri Yogawati, Ni Luh Eka; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2021)
Klungkung Regency Population and Civil Registration Office has an innovation in the field of birth certificate, namely the Bela Nanda program, this program aims to provide fast, accurate and responsive public service in the field of birth certificate. In the implementation of the program Bela Nanda in collaboration with public hospitals and health centers in Klungkung Regency. The purpose of this study is to find the performance of Disdukcapil in issuing birth certificates through the Bela Nanda program.This study based on Dwiyanto theory about performance. the results show that there are several indicators that have worked well namely accountability indicators while indicators of productivity, quality of service, responsiveness, and responsibility have worked well but not optimally such as socialization, community requirements incomplete, influenced of local culture in naming babies and no joint evaluation has ever taken. Keywords :Perfomance, Disdukcapil, Program, Bela Nanda